Correlation of Intraocular pressure and Visual Field Defects in Primary Open Angle Glaucoma - Gurung, Anu; Thapa, Kamala; Dhakal, Sachit (Medical Journal of Shree Birendra Hospital, 2022)
Aim: To correlate between intraocular pressure (IOP) with visual field pattern in primary open angle glaucoma (POAG). Methods: Pretreatment IOP at presentation was measured in 94 eyes of patients diagnosed with POAG in a descriptive correlational study. At least two Humphrey Visual Field(HVF) assessment two weeks apart was performed. Glaucomatous visual field defect and its severity was diagnosed on the basis of Hodapp-Parrish-Anderson criteria. The relationship between visual field defect and IOP were analyzed. Results: Superior arcuate scotoma was most common visual field defect seen in 18(19.1%) eyes. 56 eyes (59.6%) had mild POAG (MD of <-6dB) with no cases having double arcuate scotoma whereas 1 eye (16.0%) with moderate POAG (MD of -6 to -12dB) had 1 double arcuate scotoma and 23 eyes (24.5%) with severe POAG (MD of >-12dB) had 14 double arcuate scotoma. The mean IOP in mild POAG was 24.29 mmHg (range 21-30); 26.40mmHg (range 22-31) in moderate POAG and 29.70 mmHg (range 22-36) in severe POAG. Significant relation was demonstrated between elevated IOP at presentation and higher negative values of MD (p<0.001). Conclusions: Higher IOP at presentation is associated with severity of POAG. Aggressive treatment should be initiated to arrest the rate of progression.